2008
DOI: 10.1038/jp.2008.108
|View full text |Cite
|
Sign up to set email alerts
|

Massage therapy reduces hospital stay and occurrence of late-onset sepsis in very preterm neonates

Abstract: Objective: To study the effect of maternal massage therapy on hospital stay in very-low-birth-weight infants who were already submitted to skin-toskin care.Study Design: A randomized study was performed including infants of birth weight X750 and p1500 g and gestational age p32 weeks. The exclusion criteria were as follows: death before completing 48 h and presence of major malformations. Neonates were divided into intervention group (IG) (standard care plus maternal massage) and control group (CG). Anthropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 29 publications
(29 reference statements)
3
59
0
4
Order By: Relevance
“…The study selection process is outlined in the Figure. Of the 11 studies, 2 evaluated infant massage, 25,31 5 GHT, 46,50-53 2 TAC-TIC therapy, 48,54 1 social stimulation including touch, 49 and 1 therapeutic touch. 45 A range of study methodologies was reviewed, including random ized controlled trials (RCTs), 25,45,[50][51][52][53] follow-up outcomes of these RCTs, 31,52 pretest/ posttest time series interrupted design, 48,54 a quasiexperimental, 46 and an observational, counterbalanced across-session and infants design. 49 Of the and improved neurologic, motor and behavioral development [29][30][31][32] ), many of the existing studies have varying protocols, are limited to healthy or convalescing preterm infants greater than or equal to 32 weeks' postmenstr ual age (PMA), and are seldom contingent on infant cues.…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%
“…The study selection process is outlined in the Figure. Of the 11 studies, 2 evaluated infant massage, 25,31 5 GHT, 46,50-53 2 TAC-TIC therapy, 48,54 1 social stimulation including touch, 49 and 1 therapeutic touch. 45 A range of study methodologies was reviewed, including random ized controlled trials (RCTs), 25,45,[50][51][52][53] follow-up outcomes of these RCTs, 31,52 pretest/ posttest time series interrupted design, 48,54 a quasiexperimental, 46 and an observational, counterbalanced across-session and infants design. 49 Of the and improved neurologic, motor and behavioral development [29][30][31][32] ), many of the existing studies have varying protocols, are limited to healthy or convalescing preterm infants greater than or equal to 32 weeks' postmenstr ual age (PMA), and are seldom contingent on infant cues.…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%
“…14,17,33---35 In some studies, only the mothers provided KTS. 16,35,36 Ferber et al 15 suggested that during the first ten seconds of TS, the caregiver should only rest his hand on the PI, avoiding movements.…”
Section: Resultsmentioning
confidence: 98%
“…Compared to control group in which infants have not been massaged, previous studies reported that on average, preterm infants who had a 10-day massage gained more weight and were discharged 3-6 d sooner [22,23] . However, a later study showed that newborns after maternal massage were discharged 7 d before the group without massage therapy, which would generate significantly lower hospital costs [24] .…”
Section: Massage and Preterm Neonatesmentioning
confidence: 99%